Monitoring subjective well-being: Some new empirical evidence for Germany - Erich Oltmanns; Albert Braakmann; Joachim Schmidt (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
What is subjective well-being influenced by? Since the Report by the Commission on the Measurement of Economic Performance and Social Progress by Stiglitz, Sen and Fitoussi a huge number of studies has raised this question - with partly different findings. In addition, international organizations are increasingly addressing subjective well-being issues. The post-2015 development agenda of the United Nations as well as the inclusive growth strategy of the OECD may be quoted as examples. Facing the current state of national and international discussion, this paper analyses appropriate indicators for the mostly named factors influencing subjective well-being. The goal of the empirical study for Germany is twofold: First of all, the indicators discussed prominently are analysed with regard to the relevance for explaining the degree of subjective well-being (micro level). Secondly, it is examined, whether the relevance of these indicators changes over time. The empirical results presented in this paper are mainly based on yearly longitudinal data of private households in Germany. Currently, the data set covers about 21,000 individuals living in more than 12,000 private households. The data set provides information on various indicators for subjective well-being mentioned by most of the recent studies, like for instance people's life-circumstances and individual assessments. Concluding remarks concern on one hand the question if data from EU-SILC (because of its Europe-wide coverage) are useful in this context. On the other hand the combination of data at the micro level with indicators at the aggregate level is discussed as well.
Additional information: Paper prepared for the 33rd General Conference of The International Association for Research in Income and Wealth Rotterdam, Netherlands, August 24-30, 2014
Keywords: C2; I31; 330; gross domestic product; Stiglitz-Sen-Fitoussi-Report; quality of life; Socioeconomic Panel (SOEP); Germany